PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMISARIS INDEPENDEN, KECUKUPAN MODAL TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING - Arde Lianti; Hesty Ervianni Zulaecha; Hamdani Hamdani; Ahmad Zaki Mubbarok (FEB Universitas Maritim Semarang, 2022)
The purpose of this study was to determine the effect of leverage, profitability, company size, company age, Capital Adequacy (Capital Adequacy Ratio) and independent commissioners on Islamic social reporting (ISR). The research time period used is 6 years, namely the 2015-2020 period. The population of this research is Islamic Bank. The sampling technique used a purpose sampling technique. The type of data used is secondary data obtained from the official website of each Islamic Bank. The analysis method used is panel data regression. The results showed that leverage (DER) had a negative effect on Islamic social reporting (ISR), while profitability (ROE), company age and independent commissioners had no effect on Islamic social reporting (ISR). while company size and Capital Adequacy (Capital Adequacy Ratio) have a significant effect on the disclosure of Islamic Social Reporting (ISR) at Islamic Bank in Indonesia and Then together, the variable leverage (DER), profitability (ROE), company size, company age, Capital Adequacy and independent commissioners have an effect on Islamic social reporting (ISR).